Neutrophil-like Cell-Membrane-Coated Nanozyme Therapy for Ischemic Brain Damage and Long-Term Neurological Functional Recovery - Feng, Lishuai; Dou, Chaoran; Xia, Yuguo; Li, Benhao; Zhao, Mengyao; Yu, Peng; Zheng, Yuanyi; El-Toni, Ahmed Mohamed; Atta, Nada Farouk; Galal, Ahmed; Cheng, Yingsheng; Cai, Xiaojun; et al. (ACS nano, 2021)
Oxidative stress and a series of excessive inflammatory responses are major obstacles for neurological functional recovery after ischemic stroke. Effective noninvasive anti-inflammatory therapies are urgently needed. However, unsatisfactory therapeutic efficacy of current drugs and inadequate drug delivery to the damaged brain are major problems. Nanozymes with robust anti-inflammatory and antioxidative stress properties possess therapeutic possibility for ischemic stroke. However, insufficiency of nanozyme accumulation in the ischemic brain by noninvasive administration hindered their application. Herein, we report a neutrophil-like cell-membrane-coated mesoporous Prussian blue nanozyme (MPBzyme@NCM) to realize noninvasive active-targeting therapy for ischemic stroke by improving the delivery of a nanozyme to the damaged brain based on the innate connection between inflamed brain microvascular endothelial cells and neutrophils after stroke. The long-term in vivo therapeutic efficacy of MPBzyme@NCM for ischemic stroke was illustrated in detail after being delivered into the damaged brain and uptake by microglia. Moreover, the detailed mechanism of ischemic stroke therapy via MPBzyme@NCM uptake by microglia was further studied, including microglia polarization toward M2, reduced recruitment of neutrophils, decreased apoptosis of neurons, and proliferation of neural stem cells, neuronal precursors, and neurons. This strategy may provide an applicative perspective for nanozyme therapy in brain diseases.